Modellierung kinetisch kontrollierter, turbulenter Flammen für Magerbrennkonzepte - Kern, Matthias (KIT Scientific Publishing, 2013)
The design of technical combustion systems demands efficient as well as precise models correctly predicting the interaction of turbulence and combustion. Main focus of this work is to develop and evaluate turbulent combustion models applicable for the simulation of modern lean combustion concepts using gaseous or liquid fuels. Within this work these models are both validated on model flames and applied to technical systems.